2017
DOI: 10.1016/j.expneurol.2016.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Models of axon regeneration in Drosophila

Abstract: Maintaining neuronal connectivity in the face of injury and disease is a major challenge for the nervous system. The great length of axons makes them particularly vulnerable to insult with dire consequences for neuronal function. In the peripheral nervous system there is a program of axonal regeneration that can reestablish connectivity. In the mammalian central nervous system, however, injured axons have little or no capacity to regenerate. The molecular mechanisms that promote axon regeneration have begun to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 73 publications
0
23
0
Order By: Relevance
“…These studies are revealing evolutionary conserved molecular mechanisms. Nmnat is involved in maintaining axonal integrity (Fang and Bonini, ; Soares et al, ), and the DLK‐JNK and PTEN‐Akt signaling pathways can promote axonal re‐growth (Song et al, ; Brace and Diantonio, ). The involvement of glial cells in axonal regeneration has been little investigated.…”
Section: Drosophila Comes Of Age As a Model Organism To Investigate Rmentioning
confidence: 99%
“…These studies are revealing evolutionary conserved molecular mechanisms. Nmnat is involved in maintaining axonal integrity (Fang and Bonini, ; Soares et al, ), and the DLK‐JNK and PTEN‐Akt signaling pathways can promote axonal re‐growth (Song et al, ; Brace and Diantonio, ). The involvement of glial cells in axonal regeneration has been little investigated.…”
Section: Drosophila Comes Of Age As a Model Organism To Investigate Rmentioning
confidence: 99%
“…To study dendrite recovery from injury, we needed to enable animals to survive multiple imaging sessions and fully recover. Whereas it is possible to repeatedly image the wings of intact adults to study the regeneration of axons of wing neurons after injury (Soares et al 2014;Brace and DiAntonio 2017), those wing neurons are unsuitable for examining dendrite architecture because they lack complex dendritic arbors.…”
mentioning
confidence: 99%
“…In the PNS, the JNK signalling pathway is activated in response to axon injury in damaged neurons, where it regulates injury-induced transcriptional changes (Xiong et al, 2010). The activation of this signalling pathway in the damaged neuron can promote axonal re-growth (Brace and DiAntonio, 2017;Song et al, 2012). In addition, it has been shown that axon self-destruction leads to the activation of Draper/Ced-1/MEGF-10.…”
Section: Activation Of Jnk Signalling In Glia Cells Is Necessary But mentioning
confidence: 99%